A prospective randomized comparative placebo-controlled double-blind study in two groups to assess the effect of the use of biologically active additives with Siberian fir terpenes for the biological age of a person - Maganova, Faniya; Voevoda, Mikhail; Popov, Vladimir; Moskalev, Alexey (Frontiers in Pharmacology, 2023)
A prospective randomized comparative placebo-controlled double-blind study was carried out based on Arterial Indices model of biological age. The study involved 60 men and women aged 40-65 years that were randomly divided into two equal groups of 30 people: the main group and the control one. The study participants from the main group received a dietary supplement containing Siberian fir terpenes, limonene, alpha-linolenic acid, and vitamin E - 1 capsule 3 times a day for 90 days. Patients in the comparison group received a placebo according to a similar scheme. Anthropometric and biochemical characteristics of patients from both groups have not undergone any significant changes. According to ultrasound examination of the carotid arteries, we observed a statistically significant decrease in the minimum thickness of the intima-media complex (by 45%). The maximum carotid artery stenosis on the right or left and the expansion index in patients of both groups did not change significantly during treatment. According to the results of applanation tonometry, it was revealed that when taking the studied dietary supplement, the pulse wave velocity significantly decreased compared to the initial one (by 10%). Accordingly, the Arterial Indices biological age decreased by 2.5 years compared to the baseline level in patients of the main group and did not change in patients from the comparison group. Supplementation of fir terpenes in middle-aged patients of both sexes reduces the biological age reflecting the condition of the arteries.